Minocycline susceptibility breakpoints for Acinetobacter baumannii: do we need to re-evaluate them?. (8th November 2018) - Tsakris, Athanasios; Koumaki, Vasiliki; Dokoumetzidis, Aristides
Abstract: Minocycline is an old broad-spectrum tetracycline indicated for the treatment of various infections, including those due to minocycline-susceptible Acinetobacter spp. Susceptibility data worldwide are showing increasing rates of resistance of Acinetobacter baumannii to almost all antimicrobial classes, whereas minocycline seems to remain relatively potent against this significant pathogen. Since no new effective drugs have been released against MDR A. baumannii, minocycline is an attractive choice. Tracing back minocycline CLSI susceptibility breakpoints, it is evident that they have been based on old pharmacokinetic approaches. In an attempt to integrate the scarce new pharmacodynamic data, a Monte Carlo simulation was performed. It seems that the currently used breakpoints are, 8-fold elevated according to the approved dosage regimen, giving erroneously higher rates of minocycline susceptibility of A. baumannii. Therefore, current minocycline breakpoints merit re-evaluation in order to deliver reliable susceptibility profiles for selecting the appropriate therapy.